Skill level of rural leaders towards some agricultural technologies in Muda Agriculture Development Authority (MADA-Malaysia) - Masso, Wisam Yako Aziz; Man, Norsida; Mohd Nawi, Nolila (Mediterranean Center of Social and Educational Research, 2016)
Rice production in MADA is currently reaching an average of four to five tons per hectare. This figure is way better than one or two decades ago. Feder et al. (2010) state that agricultural extension has a bigger potential in improving the productivity of agricultural and also will increase the farmers’ incomes through transfer and facilitation of knowledge, skills and technologies. This study is designed to determine the perception level of skill of respondents on paddy farming technologies. The number of the respondents of this study was (260) were selected by random Sampling. SPSS software was used to analyze the data collected, statistics such as frequency, percentage, mean, standard deviation and correlation was used. The perception level of skill among respondents was moderate. The correlation was used to examine the association between Independent Variables and skill towards agriculture technologies on paddy farming. There was a significant relationship between some social, demographic factors and ‘level of skill of respondents on paddy farming technologies it is recommended that extension should give to them new training about how to apply new technologies in paddy farming.